Comando assimétrico aplicado ao conversor bridgeless para acionar leds de potência - Malschitzky, Alessandro (2018)
With the demand for electric energy growing world-wide, causing the tariff to increase and therefore the consumption needs to be optimized. In this scenario, lighting systems represent good percentage in the final bill of commerce and residences, and in both places the application can be divided into two categories: indoor and outdoor. The different categories present different needs, requiring greater versatility and applicability of the lighting systems. With all this, light-emitting diodes present themselves as the main artificial lighting technology, obtaining high luminous efficiency, yet with high useful life. However the need for a converter causes the initial cost of the application to rise considerably, making it difficult in market insertion. For this reason, the search for single-stage topologies with high efficiency, reducing the cost with the manufacturing and improving the compaction of the whole. In this work, the mathematical model of a bridgeless boost converter associated with a half bridge operating with asymmetric control will be realized. The validation of the model will be done by simulation of two converters operating in 127V and 220V, seeking a comparison between both.